Trauma-Induced Coagulopathy: Current Trends and Future Perspectives: Life sciences-Medicine - Alshammari, Faisal A.; F. Mady, Ahmed; Alharthi, Abdulrahman; Alrashedi, Talal; Alodat, Mohammed; A Alamri, Ziad; Aldhaian, Abdulmohsen (International Journal of Life Science and Pharma Research, 2023)
Trauma is a major cause of mortality all across the world. Trauma often leads to abnormal coagulation, which resultsin excessive hemorrhage. Acidosis, resuscitative hemodilution, and hypothermia are major contributory factors of traumaassociated abnormal coagulation. Abnormal coagulation has been associated with longer hospital stays, higher rate of mortality,and higher blood transfusion requirements. Previous studies have reported an early detection of coagulopathy in trauma victimsat admission to the hospital. This article aims to explore and discuss current trends in the management of trauma-inducedcoagulopathy, with a focus on understanding its underlying pathophysiology, potential therapies, and integrating innovativediagnostic tools and protocols into clinical practice. Damage control resuscitation and massive transfusion protocols have beenintegrated into managing the aforementioned hemostatic dysfunction; thromboelastography has gained renewed interest as arapid, point-of-care test to guide therapy. The objectives of this paragraph are to highlight trauma as a significant global cause ofmortality, emphasize the association between trauma and abnormal coagulation, discuss contributory factors to trauma-inducedcoagulopathy, and provide insights into current trends in its management, including early detection, damage controlresuscitation, massive transfusion protocols, and the role of thromboelastography as a point-of-care test. This point-of-viewarticle discusses current trends in trauma-induced coagulopathy management.